OPTIMIZATION OF RUBBER PRODUCTION MANAGEMENT: CASE OF SAFACAM - NGNASSI DJAMI ASLAIN BRISCO; DOKA YAMIGNO SERGE; NZIE WOLFGANG (International Journal of Innovations in Engineering Research and Technology, 2021)
The work presented here concerns the optimization of production management at SAFACAM in the rubber factory. To minimize unproductive time and avoid misuse of resources by improving profitability we have set ourselves the goal of reducing production losses on the production line and setting up a production management method for better monitoring of material consumption, propose a way to optimize production times. To do this we first made an inventoryof fixturesof the production management system through the survey sheets that we had established to identify the deviations from the standards, the evaluation of these records. The survey was done using the Kiviat diagram, allowing us to focus our work on productionlosses, material consumption monitoring, information flow management, personnel management and management maintenance. We have established a production management procedure to solve the problem of production losses, then we have suggested and led the implementation of the MRPII method based on the calculation of needs for the monitoring of the production and consumption of materials. Estimated gains on non-production are valued at 48965.42 USD